Guide for the Volunteer English Teacher - National Association for Foreign Student Affairs, Washington, DC.; National Association for Foreign Student Affairs, Washington, DC. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1973)
This guide suggests ways in which community volunteers can assist teachers of ESL or develop independent programs where no formal ones are available. The purpose of the guide is to make opportunities known to the volunteer, to clarify the volunteer-professional relationship, suggest patterns of cooperation, help the professional visualize ways in which the volunteer can assist in a formal program, and provide the volunteer with the basic information concerning second language learning which will make it possible for this person to match enthusiasm with skill. Some charateristics of the professional and the volunteer ESL teacher are described. Ways in which the volunteer can help in conversational exercises and supplementary work are discussed, as are cultural considerations that would help the teacher understand and cope with student problems. Information is provided on the process of second language learning and on different methodologies of language teaching. An introduction to phonology, morphology, syntax, register, vocabulary, and rhetoric is also provided. A glossary of linguistic terms and a bibliography of ESL materials complete the guide. (AM)
Availability: National Association for Foreign Student Affairs, 1860 19th Street, N.W., Washington, D.C. 20009 (Postage and handling fees).
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Cultural Awareness; Cultural Differences; English (Second Language); Language Styles; Language Teachers; Morphology (Languages); Nonverbal Communication; Paraprofessional School Personnel; Phonology; Rhetoric; Second Language Learning; Syntax; Teacher Aides; Teacher Education; Teaching Guides; Teaching Methods; Vocabulary; Volunteer Training; Guides, General